The Influence Of Financial Performance And Tax Avoidance On Company Value In Mining Companies Listed On The Indonesian Stock Exchange 2017-2022 - Dinarjito, Agung (WIM Solusi Prima, 2024)
Tax avoidance is an interesting research theme to discuss. This is because it will provide benefits to the company, but on the other hand, tax avoidance is an action that tends to be detrimental to the company. People tend to think that this action is a negative action whose impact will be detrimental to the company, both in terms of financial performance and company value. This research aims to analyze whether financial performance as measured by Return on Assets (ROA) and Return on Equity (ROE) has a significant effect on company value. This research also aims to analyze whether tax avoidance has a significant effect on company value. This research is quantitative research analyzed using multiple linear regression. The research samples are mining sector companies listed on the Indonesian Stock Exchange from 2017 to 2022. The research results show that tax avoidance and financial performance have a significant effect on company value. Tax avoidance as measured by the effective tax rate has a positive effect on company value. Financial performance measured using ROA has a negative effect on company value and ROE has a positive effect on company value. This research is expected to contribute to increasing knowledge regarding the topic of tax evasion in relation to financial performance and company value. For companies, this research is expected to provide additional considerations if companies carry out tax avoidance actions.